Pengembangan LKPD Berbantuan Aplikasi Canva Berbasis Etnomatematika untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa - Wahyuni, Sri; Ilmi, Nurul Khautsar; Sari, Dira Puspita (LPPM Institut Pendidikan Nusantara Global, 2024)
This development research aims to find out; (a) Validity of LKPD assisted by the Canva application on circle material based on ethnomathematics to improve students' mathematical communication skills, (b) Practicality of LKPD assisted by the Canva application on circle material based on ethnomathematics to improve students' mathematical communication skills and (c) Effectiveness of LKPD assisted by the Canva application on material Ethnomathematics-Based Circles to Improve Students' Mathematical Communication Skills. The type of research used is Research and Development (RnD). The research model used is the 4D Model (Define, Design, Development and Disseminate). The subjects in this research were 30 class VIII students at MTs Muhammadiyah Sidomulyo. The results of this research analysis are; (a) The LKPD developed meets the valid category and the percentage value obtained is 94.25% with the criteria